Western diet promotes endometriotic lesion growth in mice and induces depletion of Akkermansia muciniphila in intestinal microbiota - Guillaume Parpex; Benoît Chassaing; Mathilde Bourdon; Pietro Santulli; Ludivine Doridot; Marine Thomas; Frédéric Batteux; Sandrine Chouzenoux; Charles Chapron; Carole Nicco; Louis Marcellin (BMC Medicine)
Abstract Background Endometriosis, affecting 10% of women in their reproductive years, remains poorly understood. Both individual and environmental unexplained factors are implicated in this heterogenous condition. This study aims to examine the influence of a Western diet on endometriosis lesion development in mice and to uncover the mechanisms involved. Methods Mice were fed either a control diet or a Western diet (high in fatty acids and low in fiber) for 4 weeks. Endometriosis was then surgically induced, and lesion development was monitored by ultrasound. After 7 weeks, the mice were sacrificed for analysis of lesion characteristics through RT-qPCR, immunohistochemistry, and flow cytometry. Additionally, the intestinal microbiota was assessed using 16S rRNA gene sequencing. Results Mice on the Western diet developed lesions that were significantly twice as large compared to those on the control diet. These lesions exhibited greater fibrosis and proliferation, alongside enhanced macrophage activity and leptin pathway expression. Changes in the intestinal microbiota were significantly noted after endometriosis induction, regardless of diet. Notably, mice on the Western diet with the most substantial lesions showed a loss of Akkermansia Muciniphila in their intestinal microbiota. Conclusions A Western diet significantly exacerbates lesion size in a mouse model of endometriosis, accompanied by metabolic and immune alterations. The onset of endometriosis also leads to substantial shifts in intestinal microbiota, suggesting a potential link between diet, intestinal health, and endometriosis development. Graphical Abstract